Szacowanie współczynników bonus-malus w ubezpieczeniach komunikacyjnych OC za pomocą estymatorów bayesowskich - Szymańska, Anna (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2007)
The basis of insurance activity is proper premium estimation. In the paper, individual net premium is calculated by means of three methods: the expected value method, the variance method, and the zero utility method. Subsequently, by means of Bayesian estimators, the bonus-malus coefficients for the premiums calculated by the three methods mentioned above were estimated and compared. The research was performed for different parameters of the number of damages distribution. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1176, s. 441-448